Isolation of Thermostable Lignocellulosic Bacteria From Chicken Manure Compost and a M42 Family Endocellulase Cloning From Geobacillus thermodenitrificans Y7 - Ma, Lingling; Zhao, Yuchun; Meng, Limin; Wang, Xin; Yi, Yanglei; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin (Frontiers in Microbiology, 2020)
The composting ecosystem provides a potential resource for finding new microorganisms with the capability for cellulose degradation. In the present study, Congo red method was used for the isolating of thermostable lignocellulose-degrading bacteria from chicken manure compost. A thermophilic strain named as Geobacillus thermodenitrificans Y7 with acid-resident property was successfully isolated and employed to degrade raw switchgrass at 60 ℃ for 5 days, which resulted in the final degradation rates of cellulose, xylan and acid-insoluble lignin as 18.64%, 12.96% and 17.21%, respectively. In addition, GC-MS analysis about aromatic degradation affirm the degradation of lignin by G. thermodenitrificans Y7. Moreover, an endocellulase gene belong to M42 family was successfully cloned from G. thermodenitrificans Y7 and expressed in E. coli BL21. Recombinant enzyme Cel-9 was purified by Ni-NTA column based the His-tag, and the molecular weight determined as 40.4 kDa by SDA-PAGE. The characterization of the enzyme Cel-9 indicated that the maximum enzyme activity was realized at 50 ℃ and pH 8.6 and, Mn2+ could greatly improve the CMCase enzyme activity of Cel-9 at 10mM, which was followed by Fe2+ and Co2+. Besides, it also found that the β-1,3-1,4, β-1,3, β-1,4 and β-1,6 glucan linkages all could be hydrolyzed by enzyme Cel-9. Finally, during the application of enzyme Cel-9 to switchgrass, the saccharification rates achieved to 1.81±0.04% and 2.65±0.03% for 50% and 100% crude enzyme, respectively. All these results indicated that both the strain G. thermodenitrificans Y7 and the recombinant endocellulase Cel-9 have the potential to be applied to the biomass industry.